Gamification as a Trigger to Instill Empathy towards Historical Processes in the A levels curriculum from the area of Humanities and Social Science - Gil Ruiz, Paula (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2021)
This paper focus on exploratory research to investigate how to introduce serious games in the High School in order to know and improve our knoledge about critically assess and the realities of the world contemporary. It has been proposed to measure the empathic inclination produced by the 1979 Revolution Black Friday video game, because it exemplifies a real conflict, in a Middle Eastern country like Iran, in which different ideologies, different economic classes and different social classes come up in a revolution to change the current situation. To carry out the research, 163 reviews were collected from the Steam Social Network (STEAM, 2020), and classified as Mostly Positive. The qualitative analysis focuses on examining measurable statistics indicators generated according to the Davis (1980) interpersonal reactivity index, which includes an instrument that allows measuring individual differences in empathic tendencies from four dimensions: Perspective Taking (PT), Empathic Concern (EC), Personal Distress (PD) and Fantasy (FS). The results show how the video game responds positively to these four dimensions. 33 per cent of those review show the how they learn about historiacal events while they were playing, learning about a historical event unknown to them to date.